POLITIK HUKUM RANCANGAN PERUBAHAN KUHP - Joko Sriwidodo (Faculty of Law - Tarumanagara University, 2020)
The Criminal Code (KUHP) is a legal book that regulates criminal regulations against crimes or offenses. The Criminal Code in effect in Indonesia itself is still a colonial legacy of the Criminal Code, although it has undergone several reforms to revoke, add and refine articles in the Criminal Code, for example Law no. 1 of 1946 concerning Criminal Law Regulations, Law no. 7 of 1974 concerning Control of Gambling and several other laws and regulations. Systematics of the Criminal Code consists of 3 books with 569 articles. Because our KUHP still uses the KUHP from colonial heritage, it is necessary to amend the KUHP (RUU KUHP) so that it contains more local wisdom values and the development of Indonesian society. In making amendments to the Criminal Code, Indonesia as a democratic rule of law involves the DPR (Parliament) and the Government. Because these changes have to go through discussions between the DPR and the Government and must be included in the Prolegnas. The problems that will be examined in this research are: (1) How is the Political Law of Changing the Law in Indonesia ?, (2) How is the Political Law of the Draft Amendment to the Criminal Code in Indonesia ?. This paper wants to try to provide an overview of the Political Law of the Draft Amendment to the Criminal Code in Indonesia, both in the normative theory of law and in practice. This research is a normative legal research conducted through library research by conducting studies and analyzing primary, secondary and tertiary legal materials. In this writing, the researcher also carried out observation activities on the Political Law in the Draft Amendment of the Criminal Code, the public response to the Draft Amendment to the Criminal Code.